2000
DOI: 10.1046/j.1442-2042.2000.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pheochromocytoma arising in the spermatic cord 5 years after removal of bilateral carotid body tumors and adrenal pheochromocytomas

Abstract: A patient with ectopic pheochromocytoma that developed in the spermatic cord about 5 years after successive resections of bilateral carotid body tumors and bilateral adrenal pheochromocytomas is reported. This is thought to be the first case of pheochromocytoma of the spermatic cord in a setting of multiplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The importance of nodules of EACT in the groin should not be overstated. There have been reported cases of phaeochromocytoma developing in the groin [22], and of Cushing's syndrome associated with ectopic adrenal tissue [23], but these are very rare. In agreement with other authors, we consider it reasonable to excise a nodule of EACT found incidentally, but not to risk injuring spermatic cord structures by systematically searching for it.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of nodules of EACT in the groin should not be overstated. There have been reported cases of phaeochromocytoma developing in the groin [22], and of Cushing's syndrome associated with ectopic adrenal tissue [23], but these are very rare. In agreement with other authors, we consider it reasonable to excise a nodule of EACT found incidentally, but not to risk injuring spermatic cord structures by systematically searching for it.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is not clinically significant and also not associated with endocrine abnormalities. Nevertheless, the occurrence of pheochromocytoma and Cushing's syndrome associated with aberrant adrenal tissue has been reported [11] [12]. The patient in this case had a history of hypertension since early 40's.…”
Section: Discussionmentioning
confidence: 90%
“…Thus far, these paragangliomas have been described in middle-aged men, none of whom has had genetic testing, although one patient clearly had evidence of multiple tumours, for which we would strongly recommend systematic candidate gene mutation analysis [11]. Until about 10 years ago, pheochromocytomas and paragangliomas were known to occur in the context of various tumour syndromes, including multiple endocrine neoplasia type 2 (MEN 2), VHL disease, and NF1.…”
Section: Discussionmentioning
confidence: 99%